THE METHODOLOGY AND TECHNIQUE IN ENGLISH LANGUAGE TEACHING FOR THE HEARING - IMPAIRED STUDENTS AT SLB.B SIDAKARYA DENPASAR - FERRYANTI, NI PUTU (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2016)
ABSTRACT English language is an International language. Every country has to learn it in order to ease the communication among countries. The English language teaching is also given for those who has serious problem with their acoustic medium. This research is aimed to investigate and analyze the effective and appropriate English language teaching methodology used by the teacher in SLB.B Sidakarya, Denpasar- Bali. The field work research was conducted to obtain the data in SLB.B Sidakarya Denpasar. The data was analyzed qualitatively and presented in descriptive and narrative ways. The methodology and techniques in teaching English language for the hearing-impaired students seem to be different from the normal one, hence the teacher has to apply the effective and appropriate methodology and techniques in order to ease them comprehending the English language. Regarding the disability of the hearing-impaired students, the teacher had to use sign language and total body movement to support the methodology and techniques in English language teaching.Key words: English language, methodology, technique